Primary Pulmonary Choriocarcinoma After Human Chorionic Gonadotropin Normalization Following Hydatidiform Mole A Report of Two Cases - Maestá, Izildinha [UNESP]; Leite, Fabio Vicente; Michelin, Odair Carlito; Rogatto, Silvia Regina [UNESP] (Sci Printers & Publ Inc, 2010)
BACKGROUND: Primary pulmonary choriocarcinoma (PPC) is rare and frequently leads to death.CASES: Two young patients presented with previous molar pregnancy and spontaneous serum human chorionic gonadotropin (hCG) normalization. Patient 1 was referred to our center after partial response to chemotherapy. Pulmonary lobectomy was performed, and hCG rapidly declined. During further chemotherapy, liver metastasis was detected by positron emission tomography. Right hepatectomy was performed, and hCG declined for 28 days, but increased again despite chemotherapy. This patient died from hepatic failure 3 years after diagnosis. Patient 2 presented with persistently high hCG, though the affected organ was not identified. Chemotherapy was unsuccessful. Patient reevaluation showed an isolated pulmonary mass. Pulmonary lobectomy was performed; 2 weeks later, hCG was normal and consolidation with 2 cycles of chemotherapy was administered. The patient has been in remission for 24 months. PPC was confirmed by histo pathology and immunohistochemistry in both cases. Gestational origin of the tumor was confirmed by molecular genetic analysis (polymorphic microsatellite markers).CONCLUSION: The possibility of choriocarcinoma cannot be overlooked in young women with an isolated pulmonary mass. Early diagnosis, prompt chemotherapy, and surgical resection in a specialized center improves the prognosis. (J Reprod Med 2010;55:311-316)
Keywords: genetic origin; primary pulmonary choriocarcinoma; salvage therapy